Implications of the NonCommercial (NC) Restriction for Educational Content Licensed Under a Creative Commons (cc) Licence - Keats, Derek (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2006)
Individuals and institutions are increasingly making content available under Creative Commons (cc) licences. Creative Commons licences are heterogeneous, even though common discourse often assumes homogeneity. A cc licence that is analogous to the free software licence of the GNU General Public Licence is the cc Attribution-ShareAlike (BY-SA) licence. An informal survey of content on the Internet indicates that less than 24% of educational content uses this licence. Seventy-three per cent of content surveyed uses a cc NonCommercial (NC) restriction on use. Casual conversations with authors who use cc licences indicate that most do not understand the implications of choosing a particular licence. A set of principle-based guidelines for choosing cc licences for educational content is suggested.